2016
DOI: 10.2147/vhrm.s106534
|View full text |Cite
|
Sign up to set email alerts
|

Detection of peripheral arterial disease with an improved automated device: comparison of a new oscillometric device and the standard Doppler method

Abstract: In occidental countries, peripheral arterial disease (PAD) is an important health issue; however, most subjects are asymptomatic (~50%) and therefore undiagnosed and untreated. Current guidelines recommend screening for PAD in primary care setting using ankle brachial index (ABI) in all patients with cardiovascular risks. This is, however, not performed strictly because the standard Doppler method is cumbersome and time-consuming. Here, we evaluate the accuracy and reproducibility of ABI measurements obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 18 publications
(25 reference statements)
0
22
0
Order By: Relevance
“…[ 9 ] However, the accuracy of instruments is different depending on instrument type, general practice population, severity of PAD patients, and cutoff point. [ 10 11 ] This study examined patients at risk of PAD in a hospital setting with different criteria from previous studies. This study used blood pressure (BP) measurement (oscillometric BP, Terumo, ES-P600) to manually calculate ABI values as compared with an automated ABI (VP-2000/1000 Type 230, oscillometric method).…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] However, the accuracy of instruments is different depending on instrument type, general practice population, severity of PAD patients, and cutoff point. [ 10 11 ] This study examined patients at risk of PAD in a hospital setting with different criteria from previous studies. This study used blood pressure (BP) measurement (oscillometric BP, Terumo, ES-P600) to manually calculate ABI values as compared with an automated ABI (VP-2000/1000 Type 230, oscillometric method).…”
Section: Introductionmentioning
confidence: 99%
“…Demographic data indicates that over 20% of the population of Western Europe aged over 65 have symptoms or features of ischemia, which is confirmed by the ABI tests conducted by Span et al [12].…”
Section: Discussionmentioning
confidence: 52%
“…Similarly, the research conducted by Ramos et al (2,903 men and 3,269 women) confirmed that male patients with lower extremity arteriosclerosis had lower ABI values [11]. Finnish scientists reported some slight differences in this subject, too [12].…”
Section: Discussionmentioning
confidence: 71%
“…Among the potential Doppler ABI limitations that could be avoided with use of automatic measurements, time restraint seems evident. Studies that compared time needed to perform both methods found that the average time needed for automatic oscillometric measurements was significantly lower than in Doppler measurements [ 34 , 35 ]. In the study by Špan et al, the measurements performed by Doppler were seven times longer than the automatic ones [ 35 ].…”
Section: Resultsmentioning
confidence: 99%